Development of STEM-Based E-Module to Enhance Science Literacy and Science Process Skills in Chemistry Learning - Seget Tartiyoso (Jurnal Penelitian Pendidikan IPA, 2025)
This research investigated the development and implementation of a STEM-based electronic module (e-module) designed to enhance science literacy and science process skills among high school students in chemistry learning. The study employed a qualitative analysis approach to examine the design process, implementation challenges, and educational outcomes of integrating Science, Technology, Engineering, and Mathematics principles into digital chemistry learning materials. Results indicate significant improvements in students' scientific explanation abilities and experimental design skills, suggesting that well-designed STEM-based e-modules can effectively bridge theoretical understanding with practical applications in chemistry education.